Encouraging The Growth Of Msmes (Micro, Small And Medium Enterprises) Through E-Commerce - Sabrina Diva Nur Rahmadani; Hendri Hermawan Adinugraha; Muhammad Shulthoni (Universitas Islam Negeri (UIN) Salatiga, 2024)
This research aims to analyze the impact and challenges of e-commerce implementation for the growth of MSMEs as well as to develop concrete solutions and practical guidelines to increase the utilization of e-commerce among MSMEs. The research method used is a descriptive qualitative approach with data collection from various sources. The results show e-commerce has a significant positive impact on MSME growth, but there are still challenges such as access to technology and understanding of e-commerce management. Proposed solutions include improved digital literacy, training, government support and clear regulations. The implication is to provide insights for MSMEs, stakeholders and government to overcome challenges and capitalize on e-commerce opportunities.